P0033 Significance of patterns of failure after treatment with curative intent in adenocarcinoma of stomach. (July 2015) - Prameela, C.G.; Ravind, R.; Dinesh, M.
Abstract : Background: Improved overall and relapse-free survival with adjuvant loco-regional radiotherapy augmented by concurrent chemotherapy using fluorinated pyrimidines has been shown in adenocarcinoma of stomach. Adjacent critical organs can be spared without compromising dose to target using 3D conformational radiotherapy, and intensity-modulated radiotherapy has failed to document any added advantage. The aim of this retrospective analysis was to assess outcome and patterns of failure in all patients with non-metastatic adenocarcinoma of stomach, including gastro-oesophageal junction, who received adjuvant postoperative chemoradiotherapy between 2006 and 2013. Methods: Electronic medical records and radiotherapy records were retrieved and analysed. Patterns of failure were evaluated. The primary endpoint was overall survival. Findings: There were 73 cases. Male to female ratio was 57:16 (78.1%:21.9%). Median age of presentation was 57 years (range 27–73). Median follow up was 52.27 months. 50.7% of cases had poorly differentiated tumours. Pathological stage distribution was as follows: stage IA 1.4%, stage IB 8.2%, stage IIA 19.2%, stage IIB 26%, stage IIIA 20.5%, stage IIIB 19.2%, and stage IIIC 5.5%. All patients had undergone total or partial gastrectomies. Concurrent chemotherapy was based on fluorouracil. Radiotherapy was planned using 3D-conformal, six-field, mono-isocentric techniques, and a dose of 4500 cGy in 25 fractions was delivered. Median overall survival was 27.7 months (95% confidence interval (CI) 15.48–39.92). Patients with poorly differentiated tumours had median overall survival of 19.2 months ( p = 0.0592). Pathological stage was inversely related to overall survival. For stage I tumours, 5-year overall survival was 83.33%, and for stage IIIC tumours, median overall survival was 8.53 months ( p = 0.0344). Significantly poor overall survival was associated with recurrence ( p < 0.0001). Local failure caused a worse overall survival compared with regional and distant failures (local: p < 0.0001; regional: p = 0.0170; and distant: p = 0.002). Interpretation: Loco-regional control correlates with overall survival, stressing the need for aggressive treatment. Whether an escalation in radiation dose in this era of conformal planning would improve local control and overall survival needs to be explored and requires robust data from randomised controlled trials.